(untitled) (Revista científica Olimpia, 2020)
This article has as its main pillar, differentiated educational care in School Physical Education to schoolchildren included in indicator four of school duties, in order to contribute to the prevention of behavioral disorders. The claim for educational care for these stems from the remarkable increase in schoolchildren who are referred post-diagnostic for special school, significantly affecting the limitations that arise in the context of School Physical Education to give way to the educational component in the teaching process. That is why research aims to make curriculum adaptations that contribute to the prevention of behavioral disorders in schoolchildren with behavioral alterations since the physical education class. To achieve this goal, it was necessary to use research methods and techniques, including analysis and synthesis, the hypothetical deductive, observation, interview, experiment in its pre-experiment variant, among others. With the implementation of curriculum adaptations to the program, significant changes in the behaviour of schoolchildren were achieved research unit, which contributed to their failure to move them to the special school of behavioral disorders, demonstrating the effectiveness of the same.